The influence of teachers’ self-efficacy on work engagement: A study of preschool teachers - Lee, Xin Wei (2023)
Preschool teachers play a vital role in creating a supportive and effective learning environment, which is widely recognised in early childhood education field. However, the shortage of preschool teachers is impacting the quality of early childhood education in Malaysia. Moreover, there is limited research on relationship between preschool teachers’ self-efficacy and work engagement, despite work engagement being a critical factor of preschool teachers’ retention. Hence, this study was aimed to investigate the relationship of preschool teachers’ self-efficacy and work engagement. This study applies Job Demands-Resources (JD-R) model to examine the research questions. The hypothesis underlying posits a significant correlation between preschool teachers’ self-efficacy and work engagement. This study employed quantitative research method and Pearson correlation coefficient as research design. The study included 73 teachers from diverse range of preschools in Penang area by using convenient sampling technique. Teachers’ Sense of Efficacy Scale (TSES) by Tschannen-Moran and Woolfolk Hoy (2001) and Utrecht Work Engagement Scale (UWES-17) by Bakker and Schaufeli (2003) were the two questionnaires used in this study. The findings presented that the three subscales of teachers’ self-efficacy, which are efficacy in instructional strategies (r= 0.368, p= 0.001), efficacy in classroom management (r= 0.341, p= 0.003) and efficacy in student engagement (r= 0.415, p=